Development of The Digital-Based Business Model for Marhani Grosir - Ardi, Ardi; Baihaqi, Imam (Gema Wiralodra, 2025)
This study aims to design and develop a digital business model for Marhani Grosir based on partnerships by utilizing the Value Proposition Design (VPD) and Business Model Canvas (BMC) approaches. The main focus of the research is to understand the needs of MSME partners and consumers as the foundation for strengthening services and improving the existing cashier application for partners. The method used is a qualitative descriptive approach, with data collected through in-depth interviews with store owners, business partners, consumers, and IT technicians. The collected data were then analyzed to map the key elements in VPD and BMC, which were formulated into the design of a digital application mockup. The research findings show that MSME partners require a digital system that facilitates restocking, records transactions, and monitors inventory in real time. Consumers seek product information transparency, fast delivery services, and clear promotional features. The developed cashier application has addressed most of these needs, although challenges remain, such as the absence of multi-account features, limited integration of digital payments, and internet network barriers. This study highlights the importance of strengthening digital elements in local wholesale business models to support operational efficiency and customer loyalty. Further strategies are recommended in the form of application feature updates, improved distribution systems, and the expansion of digital-based partnerships. By adopting a user-centered approach, Marhani Grosir can enhance its competitiveness amidst the growing digital transformation of the market.